Eksistensi Perpustakaan sebagai Pemenuhan Kebutuhan Informasi Pemustaka - Yuliani, Novita; Asmara, Rini (MASALIQ, 2025)
This research is motivated by the lack of empirical studies that discuss the existence of libraries as a fulfillment of information needs, especially in the secretariat library of the West Sumatra provincial DPRD. The purpose of this study is to describe the extent of the relationship between the Existence of Libraries and the Information Needs of Users. This type of research is quantitative with a descriptive method. The population in this study were all registered users at the Secretariat Library of the West Sumatra Provincial DPRD. Samples were taken using simple random sampling, and data were collected through observation, interviews, and questionnaires. The results of the analysis showed that the existence of the library was in the good category with an average score of 3.01. The information needs of users were in the good category with an average score of 2.93. Based on the Pearson correlation test, it showed a positive relationship between the existence of the library and the information needs of users of 0.643, including in the interval scale of 0.60-0.799. This shows that the existence of the library has a significant relationship with the information needs of users. These results emphasize that the existence of libraries has a direct influence on the information needs of users, especially institutional libraries where users are members of the institution who have jobs in certain categories.